NH3 AND NO INTERACTION WITH SI(100)-(2X1) SURFACES - Fauster, Thomas; et al. (Physical Review B, 1991)
The adsorption of NH3 and NO on Si(100)-(2 x 1) surfaces at room temperature and the stepwise nitridation have been studied by high-resolution Si 2p core-level photoemission spectroscopy. Both molecules adsorb dissociatively, but only for NO does a reaction occur beyond the first monolayer. For the growth of stoichiometric silicon nitride, annealing to 1200 K is necessary.